Media image of the government administration: Analysis of the issue of published articles on the base chosen in „Gazeta Wyborcza” and „Rzeczpospolita” in the first quarter of 2011 - Molenda, Artur (Journal of Public Governance, 2013)
The article is presenting findings, of which analysis of the media image of the Polish government administration was a purpose. Published articles constitute the research material found in „Gazeta Wyborcza” and „Rzeczpospolita” in the first quarter of 2011 which contents described and commented the current activity of the government’s part of the public sector. The author’s deliberations are concentrating on in what way and what circumstances the image of the civil service is confirmed, modified and shaped through the prism of the all-Polish press in processes of the media communication with readers/citizens. For that purpose the author checked the press enunciations concerning the activity and functioning of two chosen ministries and of two central offices, pointing at essential tendencies in forms of the media image of the public sector. The article is the edited excerpt of the post-graduation work of management in the civil service written for MSAP in 2011, in which the author also subjected the presence of the local selfgovernment at the media map of the polish public administration and also analysed meaning of the influence of historical, social and cultural contexts and conditioning on the current image of the Polish public sector.